Evidence-building and evaluation in government - Newcomer, Kathryn E. 1949-; Hart, Nicholas (Los Angeles Sage, 2022)
Public managers, contractors, and grantees conducting evaluations for government operate in a complex environment where policymakers and commissioners of evaluation expect different types of "evidence" and simultaneously employ different criteria in judging the quality of that evidence. This text provides a road map for evaluators doing business within or for government, and public managers who are expected to assess and use evidence generated by a large variety of evaluation approaches. The book provides checklists and how-to guidance to help students and other readers develop skills in important activities such as: assessing the quality of evidence claims; developing theories of change to guide the design and evaluation of programs and policies; developing learning agendas to bridge the gap between evidence producers and potential evidence users; and increasing the support of public leaders and executives in the generation and use of evidence to inform their decision-making. The authors include end-of-chapter exercises for readers to test their ability to apply the skills described.
Chapter 1 The evidence-building mandate -- Chapter 2 Assessing the quality of evidence -- Chapter 3 Employing evaluative thinking -- Chapter 4 Developing learning agendas for public organizations -- Chapter 5 Building capacity to generate and supply evidence -- Chapter 6 Building capacity to use evidence -- Chapter 7 Sustaining momentum for evidence-building capacity in government -- References -- Index.
Includes bibliographical references and index.
Keywords: Public administration -- Evaluation; Administrative agencies -- Evaluation; Organizational effectiveness; Government accountability